Design and experimental study of small axial ducted fans - Tan, Chuan Huat. (2009)
A design method based on free vortex methodology is developed. Three dimensional fan models are generated by stacking two dimensional cascades. 5 rotors and 4 stators were designed and fabricated and their performance were compared to an existing fan rotor and stator. Rotor Rl was taken to be the basic design and the rest of the rotors were designed with a distinctive parameter to investigate the effects of dihedral angle (rotor R2), blade chord length (rotor R3), number of blades (rotor R4) and camber angle (rotor R5) on the performance characteristics of the fan. Rotor Rl with an axial blade chord length of 12.5 mm, zero dihedral, 6 blades and 25 degree constant camber was found to have the best performance as compared to the other models. A 40 per cent increment in the static head over the existing rotor at the operating point was achieved. Following are other major findings